2018
DOI: 10.1186/s41984-018-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy in malignant middle cerebral artery infarctions: outcome of 25 cases

Abstract: Background: Large space-occupying middle cerebral artery (MCA) infarctions with signs of elevated intracranial pressure and brain herniation have overall mortality rates of 80%. Several studies have suggested that decompressive surgery reduces mortality and improves outcome of these patients. Aim: The aim of this study was to evaluate the clinical and radiological outcome of decompressive craniectomy in the setting of malignant MCA infarctions. Patients and method: This is a prospective study conducted on pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A recent paper showed that decompressive craniectomies for malignant MCA infarct patients still had severe disability despite improvement in mortality (3). Early surgical intervention within 6 hours from deterioration or significant radiological findings were found to be significant predictor of favourable clinical outcome in a separate study (4). Although current evidence shows the benefit of surgical intervention by reducing mortality, information is still lacking on patient selection and the impact of surgery on the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper showed that decompressive craniectomies for malignant MCA infarct patients still had severe disability despite improvement in mortality (3). Early surgical intervention within 6 hours from deterioration or significant radiological findings were found to be significant predictor of favourable clinical outcome in a separate study (4). Although current evidence shows the benefit of surgical intervention by reducing mortality, information is still lacking on patient selection and the impact of surgery on the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%